Depresi Postpartum Berhubungan dengan Motivasi Pemberian Asi Ekslusif Satu Bulan Pertama pada Bayi - Islamiyah Islamiyah; Umi Rachmawati Wasil Sardjan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the relationship between postpartum depression and the motivation of exclusive breastfeeding for the first month of infants. This research is observational research with a cross-sectional study design with a quantitative approach. The study results using the Mann Whitney test, the significance value indicated a p-value of 0.000. In conclusion, there is a relationship between postpartum depression and mothers' motivation in exclusive breastfeeding in the first month. Keywords: Exclusive Breastfeeding, Postpartum Depression, Breastfeeding, Motivation